Facilitating Social Interactions With Peers in Specialized Early Childhood Settings for Young Children With ASD. Issue 2 (1st June 2019) - Hume, Kara; Sam, Ann; Mokrova, Irina; Reszka, Stephanie; Boyd, Brian A.
Abstract: Young children on the autism spectrum have minimal social interaction with their peers in inclusive preschool settings, thus limiting opportunities to build social relationships. Research indicates that explicitly training peers how to interact with classmates with autism spectrum disorder (ASD) can increase the likelihood of peer-directed behavior; however, less is known about other strategies that can be used to support the peer-related social interactions of children with ASD and how those strategies may be used in conjunction with trained peers. Video data were analyzed from 23 classrooms using the Learning Experiences and Alternative Program for Preschoolers and Their Parents model (an inclusive preschool program that emphasizes peer training and peer support) to provide a snapshot of environmental features and the role of implementation fidelity that may enhance or inhibit the social interaction of 52 children with ASD. Findings indicate that social interaction is most likely to occur when an adult is not present, during small group activities, pretend play, and large motor activities. Implications for practice are discussed.